Safety helmet - Ahmad Noordin, Noor Farah Hanis; Ab Rahman, Nur Najihah; Othman, Siti Amira (Penerbit UTHM, 2020)
In many industrial working environments, for example, mining, power, construction, and forestry, the risk of head injury that is totally encased in bone to workers is always being heard. The importance of wearing safety helmet is being supported by OSHA Standard 1910.135 which states that “The employer shall ensure that each affected employee wears a protective helmet when working in areas wherever there's a possible for injury to the top from falling objects.” In addition, the survey of accidents and injuries conducted by the American Bureau of Labor Statistics (BLS) resulted that most workers who were not wearing head protection suffered impact injuries to the head (Cynthia L Roth, 2011). There are two different type of impact protection which is type I and type II. Type I is intended to reduce the force of impact resulting from a blow only to the top of the head. This form of impact, for example, may result from a hammer or nail gun falling from above. For the type II, it is intended to reduce the force of lateral impact resulting from a blow which may be received off-center, from the side, or to the top of the head. This form of impact, for instance, could result from contact with the sharp corner of a facet beam. The most common combination is white for managers, architects, engineers, foremen or supervisors. Other onerous hat designs is also needed for a job; brown fibreglass onerous hats area unit worn by welders and different employees for top heat applications. Green typically signifies a security inspector, however is additionally used for brand new employees.